The Association of Dobutamine and Ivabradine in Heart Failure and Circulatory Choc: A Case Report and Narrative Review - Attou, Rachid; Carbognani, Daniel; Villet, Benoit; Honore, Patrick M; Bels, David De; Redant, Sébastien (Cardiology and Cardiovascular Medicine, 2020)
The authors present the case of a patient developing septic cardiomyopathy during a septic shock in whom the initiated dobutamine induced tachycardia without improvement in cardiac function. The addition of ivabradine to dobutamine restored cardiac function consistent with the septic shock situation. The authors take the opportunity to present a narrative review on the combination of dobutamine and ivabradine.